2011
DOI: 10.1016/j.biopsych.2010.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Genetic Variation Data Implicate PCLO in Bipolar Disorder

Abstract: Background Genetic variation may contribute to differential gene expression in the brain of individuals with psychiatric disorders. To test this hypothesis, we identified genes that were differentially expressed in individuals with bipolar disorder, along with nearby single nucleotide polymorphisms (SNPs) that were associated with expression of the same genes. We then tested these SNPs for association with bipolar disorder in large case-control samples. Methods We used the Stanley Genomics Database to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Since ARHGEF6/7 are known to bridge between GIT1 and PAKs, this reduced association may be due to alteration of the GIT1-ARHGEF6/7-PAK complex. Given the location of R283W, this variant may also affect the association of GIT1 with other key synaptic proteins associated with psychiatric disease genetic risk, such as the presynaptic cytomatrix protein PCLO (Piccolo) and PPFIA2 (Protein Tyrosine Phosphatase, Receptor Type, F Polypeptide (PTPRF), Interacting Protein (Liprin), Alpha 2) (14, 47). Another interesting question is why GIT1-S601N has similar defects to GIT1-R283W, given that S601 is located well outside of the SHD domain of GIT1 in a region with no defined structural domain.…”
Section: Discussionmentioning
confidence: 99%
“…Since ARHGEF6/7 are known to bridge between GIT1 and PAKs, this reduced association may be due to alteration of the GIT1-ARHGEF6/7-PAK complex. Given the location of R283W, this variant may also affect the association of GIT1 with other key synaptic proteins associated with psychiatric disease genetic risk, such as the presynaptic cytomatrix protein PCLO (Piccolo) and PPFIA2 (Protein Tyrosine Phosphatase, Receptor Type, F Polypeptide (PTPRF), Interacting Protein (Liprin), Alpha 2) (14, 47). Another interesting question is why GIT1-S601N has similar defects to GIT1-R283W, given that S601 is located well outside of the SHD domain of GIT1 in a region with no defined structural domain.…”
Section: Discussionmentioning
confidence: 99%
“…Intronic variants are increasingly recognized as a critical diseasecausing genetic constituent. Several large GWAS have associated intronic SNPs with hearing impairment, 44 bipolar disorder, 45 asthma, 46 and rheumatoid arthritis. 47 A recent report also associates an intronic SNP with serum level of transferrin.…”
Section: Discussionmentioning
confidence: 99%
“…A larger series of replication samples did not support this association but an exploratory analysis of the subset of samples most similar to the discovery sample yielded nearly significant association for a non-synonymous PCLO SNP (rs2522833). Although subsequent candidate gene studies have implicated this or other PCLO SNPs in depression (Hek et al, 2010;Minelli et al, 2012), bipolar disorder (Choi et al, 2011), and HPA axis function (Kuehner et al, 2011;Schuhmacher et al, 2011), the gene has not shown association in independent GWAS of MDD. A subsequent GWAS (Kohli et al, 2011) reported a significant recessive association for an SNP (rs1545843) in SLC6A15, a gene involved in transporting neutral amino acids.…”
Section: Common Genetic Variationmentioning
confidence: 99%